An Estimation Method for Thermal Conductivity in the Fluid Phase - Müller, Karsten; Arlt, Wolfgang (Journal of Chemical and Engineering Data, 2014)
An estimation method for thermal conductivity in the gas as well as in the liquid phase is presented in this work. The models are based on group contributions of the second-order. Temperature dependence could be described well if a valid reference temperature is used as an additional input parameter. For the gas phase the critical temperature was chosen as the reference temperature, and for the liquid phase the normal boiling temperature was chosen. Relative errors are within a magnitude of 10 % for the gas phase and 7 % to 14 % for the liquid phase. Estimation quality is high for small as well as for high absolute values of the thermal conductivity and independent of substance class or molecule size.